Global Perspectives on Management Consulting Competitiveness: Analyzing Knowledge Brokers’ Components - Sirin Akaraphan; Mongkolchai Wiriyapinit; Sukree Sinthupinyo (Ital Publication, 2024)
Bridging a significant gap in knowledge broker research, this study addresses the challenges and difficulties in demystifying the roles and components of Knowledge Brokers (KBs) within the management consulting context. Despite their recognized importance, the specific functions, and components of KBs in this specific sector context, known for its intensive use of knowledge, have been unexplored. This study aims to narrow the research gap by identifying key components of KB that enable the knowledge brokerage process in management consulting. Utilizing a mixed methods approach with Structural Equation Modeling (SEM) and data collection from various geographies from global perspectives, the research offers an in-depth understanding of KBs in management consulting. The research findings confirm Interpersonal Skills and Cognitive Ability, along with sub-components like Interactive Skill, Motivational Skill, Hybrid & Anomalous, Neutrality, Professional Competence and Experiential Knowledge, as critical to KBs. The findings offer original contributions to theoretical implications by narrowing the research gaps within this specific context. On the practical front, this study provides strategic insights for organizations to significantly enhance sustainable innovation by integrating external knowledge into organizational decision-making processes, which could be extendable to other industries. Furthermore, it suggests the potential to evolve traditional knowledge brokerage into technology-driven platforms and enhance the innovation ecosystem. Finally, the research findings offer the foundations for future studies on similar professional and knowledge-intensive settings, contextual influences of KBs, and the interrelationships among KB components. Doi: 10.28991/ESJ-2024-08-03-014 Full Text: PDF